Association between Lipoprotein Subfractions, Hemostatic Potentials, and Coronary Atherosclerosis. (30th August 2022) - Poropat Flerin, Tadeja; Božič Mijovski, Mojca; Jug, Borut
Abstract : Background . Dyslipidemias are associated with atherosclerotic plaque formation and a prothrombotic state, thus increasing the risk of both atherosclerotic vascular disease and atherothrombotic adverse events. We sought to explore the association between lipoprotein subfractions, overall hemostasis, and coronary calcifications in individuals at intermediate cardiovascular risk. Methods . Consecutive statin-naive individuals at intermediate cardiovascular risk referred for coronary artery calcium score (CACS) scanning were included. CACS was assessed using a 128-slice dual-source CT scanner. Traditional lipid profile, high-density lipoprotein (HDL) subfractions 2 and 3, and small dense low-density lipoproteins (sdLDL) were measured with commercially available assays. Overall hemostatic (OHP) and coagulation potentials (OCP) were measured spectrophotometrically, using fibrin aggregation curves after exposure to thrombin and recombinant tissue-type plasminogen activator, respectively. Overall fibrinolytic potential (OFP) was calculated as a difference between the two areas under curves. Results . We included 160 patients (median age 63 (interquartile range (IQR), 56-71 years, 52% women, and median CACS 8, IQR 0-173 Agatston units). HDL3 levels—but not sdLDL or hemostatic potentials—were significantly associated with CACS zero, even after adjusting for age, sex, arterial hypertension, dyslipidemia, diabetes, and smoking history (OR 0.980 (0.962-0.999), p = 0.034 ). HDL3 was also significantly associated with OCP (r = − 0.232, p adjusted for age and sex 0.037). Conclusions . In patients at intermediate cardiovascular risk, HDL3 is associated with both subclinical atherosclerosis and overall coagulation. Our findings are in line with studies reporting on an inverse relationship between HDL3 and atherosclerosis and provide one possible mechanistic explanation for the association between novel lipid biomarkers and coagulation derangements.